2015
DOI: 10.1177/0734371x15576410
|View full text |Cite
|
Sign up to set email alerts
|

Citizen Participation in Local Government Decision Making

Abstract: Engaging the public in government decision making is an important value and priority in a democratic society. Although there is research investigating public perceptions of citizen participation opportunities and efforts, little research focuses on understanding the motivations that public managers have to encourage citizen participation. This research seeks to understand the ways in which public managers' motivations are related to engaging the public in organizational decision making. We use data from two na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 75 publications
0
34
0
3
Order By: Relevance
“…It is important to investigate the perceptions of the public relating to the implementation of large scale policies 21 . The present study addresses a gap in the literature by providing insight into public perceptions of a proposed national heat protection policy for Australian schools.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to investigate the perceptions of the public relating to the implementation of large scale policies 21 . The present study addresses a gap in the literature by providing insight into public perceptions of a proposed national heat protection policy for Australian schools.…”
Section: Discussionmentioning
confidence: 99%
“…In order to introduce policies more broadly, public mobilisation is important to help support policy implementation. To date, many public policies have singularly focused on dialogue between discipline professionals and political leaders 21 . First introducing a policy proposal into the public arena can help strengthen advocacy, streamline information to the public and show areas of feedback that are receptive to public needs 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, policies and regulations can create barriers and restrictions that are sometimes a barrier to innovation (Patanakul & Pinto, 2014). In some studies identified in general, the cause of public service innovation occurred due to specific public policy (Daniels, et al, 2017;Edler & Fagerberg, 2017), transformative manager (Klimentova, 2014;Kim & Yoon, 2015), citizen involvement (Huang & Feeney, 2015;Thapa, et al, 2015). On the other hand, management influence (managers) has an impact on innovation performance, and innovation decisions usually involve managers as a screening mechanism to consider a series of external and internal factors that increase the likelihood of innovation outcomes (Banerjee & Ceri, 2016), a "manager"…”
Section: Sufficiencymentioning
confidence: 99%
“…In terms of civil society's commitment and participation, Huang and Fenney [9] argued that citizens' involvement in decisions related to policies which target them directly is likely to win more of their trust in government and to increase their willingness to comply with those decisions. Moreover, both researchers and practitioners have argued for one way to approach the decreasing trust in political parties (on a growing trend these days): prepare the governmental institutions for increasingly inviting and involving citizens in relevant political decisions as a way to answer people's wish to participate more in such decisions [10].…”
Section: Citizens' Participation In Decision-making Process For Urbanmentioning
confidence: 99%